Gendered Pathways From Child Abuse to Adult Crime Through Internalizing and Externalizing Behaviors in Childhood and Adolescence. Issue 18 (September 2017) - Jung, Hyunzee; Herrenkohl, Todd I.; Lee, Jungeun Olivia; Hemphill, Sheryl A.; Heerde, Jessica A.; Skinner, Martie L.
Gender differences in externalizing and internalizing pathways from child abuse to adult crime were examined across four waves of an extended longitudinal study ( N = 186 males and 170 females) using multiple-group structural equation modeling. Results show that child abuse was associated with both internalizing and externalizing behaviors in the elementary school years for both males and females. However, gender differences were found such that internalizing behaviors increased the risk of adult crime for females only, and externalizing behaviors increased the risk of adult crime for males only. Internalizing behaviors among males actually lessened the risk of adult crime, and externalizing behaviors were unrelated to adult crime among females. Findings confirm distinct pathways leading from child abuse to later crime for males and females, which is important for prevention and intervention strategies.